Health Downside of the Upside of Urban Life in Nepal - Dahal, Gokarna; Pokhrel, Prabha (Journal of Pharmacy Practice and Community Medicine)
Nepal is one of the ten least urbanized countries in the world but the pace of urbanization depots among the fastest ten. All most one third of the total country populations now leave in 217 municipalities and the number is surprisingly increases 7% per annum from 17.1% to 38.8% since last demographic health survey in 2011. Practices of declaration of municipalities and cities are heavily intensified by government in the name of territorial reform and the foundation for upcoming federal structure. With the promulgation of the new constitution of Nepal in 2015, Country guaranteed water and sanitation, clean and healthy environment and housing as basic rights of all citizens. But several existing municipalities lack basic minimum facilities such as drinking water, drainage system, hospital, playground, metallic road and recreation. Such scenario, suggests that a comprehensive approach should be taken to declare the new urban city and municipalities. Looking at the proposed future federal structure of the country, we suggest that more debate and deliberations are needed on to declare the new municipalities.
Keywords: Urban health; Urbanization; Impacts on health; Nepal; Rural health